1983
DOI: 10.1139/v83-472
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the dihedral angle of a crowded diselenide by X-ray crystallography and ultraviolet spectroscopy

Abstract: , 2749 (1983). Bis(di-tert-butylmethyl) diselenide (4) is the first example of a diselenide with an abnormal obtuse dihedral angle resulting from steric crowding. Its value was determined to be 112.1(3)" by X-ray crystallography, as compared with typical dihedral angles of 74-87" for other diselenides. The uv spectrum of 4 supports a similar conformation in solution. ence for conformations where the dihedral angle (C-Se-Se/ Se-Se-C) ( Fig. 1) is acute and lies within the range of 74"-87", except when constrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 5 publications
2
21
0
2
Order By: Relevance
“…However, the C-Se bond is slightly longer [2.015(4) and 1.995(4) Å ] than the expected bond length (1.93-1.97 Å ). Unlike few other sterically hindered diselenides [17], the CSe-Se-C dihedral angle is acute [82.62 (18)] and close to the theoretical value [18] of 90°which means that the steric strain is being relieved through bond lengthening rather than widening up of dihedral angle. One common observation in both the crystal structures is that, one of the aryl rings (phenyl or p-chlorophenyl) is more closely disposed towards the selenium atom than the other.…”
Section: X-ray Discussionsupporting
confidence: 62%
“…However, the C-Se bond is slightly longer [2.015(4) and 1.995(4) Å ] than the expected bond length (1.93-1.97 Å ). Unlike few other sterically hindered diselenides [17], the CSe-Se-C dihedral angle is acute [82.62 (18)] and close to the theoretical value [18] of 90°which means that the steric strain is being relieved through bond lengthening rather than widening up of dihedral angle. One common observation in both the crystal structures is that, one of the aryl rings (phenyl or p-chlorophenyl) is more closely disposed towards the selenium atom than the other.…”
Section: X-ray Discussionsupporting
confidence: 62%
“…. The C−Se and Se−Se bond lengths are also in the range of what found in most of the organic diselenides, i. e. (1.91–1.97 Å) and (2.285–2.33 Å), respectively …”
Section: Resultssupporting
confidence: 52%
“…Although the molecular structures of a number of diorgandiselenides have been reported, the majority contain aryl groups or sterically demanding alkyl groups as substituents [17]. Previous studies of diorganodiselenides have shown that the Se-Se and Se-C bond lengths are largely independent of the organic substituents and steric strain is relieved by increasing the C-Se-Se-C dihedral angle [17,18]. The phosphonioalkyl groups in 5a are not particularly sterically demanding and the dihedral angle C(22)-Se(2)-Se(1)-C(21) [62.80(4)°] is significantly lower than those with bulkier groups, which typically lie in the range 73-104° [17].…”
Section: Resultsmentioning
confidence: 99%